Genetic transformation of cork oak (Quercus suber L.) for herbicide resistance. - Alvarez, Rubén; Alvarez, José M.; Humara, Jaime M.; Revilla, Angeles; Ordás, Ricardo J. (Biotechnology letters, 2009)
The bar gene was introduced into the cork oak genome. Cork oak embryogenic masses were transformed using the Agrobacterium strain AGL1 which carried the plasmid pBINUbiBar. This vector harbours the genes, nptII and bar, the latter under control of the maize ubiquitin promoter. The transgenic embryogenic lines were cryopreserved. Varying activities of phosphinothricin acetyl transferase were detected among the lines, which carried 1-4 copies of the insert. Molecular and biochemical assays confirmed the stability and expression of the transgenes 3 months after thawing the cultures. These results demonstrate genetic engineering of herbicide tolerance in Quercus spp.
The following values have no corresponding Zotero field: accession-num: 19543858
Keywords: Acetyltransferases; Acetyltransferases: genetics; Acetyltransferases: metabolism; Gene Dosage; Genomic Instability; Herbicide Resistance; Herbicides; Herbicides: toxicity; Plant Proteins; Plant Proteins: genetics; Plant Proteins: metabolism; Plants, Genetically Modified; Plants, Genetically Modified: drug effects; Plants, Genetically Modified: genetics; Plants, Genetically Modified: physiology; Plasmids; Promoter Regions, Genetic; Quercus; Quercus: drug effects; Quercus: genetics; Quercus: physiology; Rhizobium; Rhizobium: genetics; Transformation, Genetic; Zea mays; Zea mays: genetics

Genetic transformation of cork oak (Quercus suber L.) for herbicide resistance. - Alvarez, Rubén; Alvarez, José M; Humara, Jaime M; Revilla, Angeles; Ordás, Ricardo J (Biotechnology letters, 2009)
The bar gene was introduced into the cork oak genome. Cork oak embryogenic masses were transformed using the Agrobacterium strain AGL1 which carried the plasmid pBINUbiBar. This vector harbours the genes, nptII and bar, the latter under control of the maize ubiquitin promoter. The transgenic embryogenic lines were cryopreserved. Varying activities of phosphinothricin acetyl transferase were detected among the lines, which carried 1-4 copies of the insert. Molecular and biochemical assays confirmed the stability and expression of the transgenes 3 months after thawing the cultures. These results demonstrate genetic engineering of herbicide tolerance in Quercus spp.
Keywords: Acetyltransferases; Acetyltransferases: genetics; Acetyltransferases: metabolism; Gene Dosage; Genomic Instability; Herbicide Resistance; Herbicides; Herbicides: toxicity; Plant Proteins; Plant Proteins: genetics; Plant Proteins: metabolism; Plants, Genetically Modified; Plants, Genetically Modified: drug effects; Plants, Genetically Modified: genetics; Plants, Genetically Modified: physiology; Plasmids; Promoter Regions, Genetic; Quercus; Quercus: drug effects; Quercus: genetics; Quercus: physiology; Rhizobium; Rhizobium: genetics; Transformation, Genetic; Zea mays; Zea mays: genetics

ENSAYO DE TRATAMIENTOS HERBICIDAS EN CULTIVO DE TRES ESPECIES FORESTALES (P. halepensis, P. nigra y Q. ilex) EN VIVERO - CARRASCO MANZANO, I; OCAÑA BUENO, L; PEÑUELAS RUBIRA, J L; DOMÍNGUEZ LERENA, S (II Congreso Forestal Español, 1997)
Weeds are one of the problems which more economic costs originates in forest nurseries due to their effect on crop growth. In spite of this, the effect of weeds on forest seedlings and their control in the nursery have not been much studied. In this study we have analysed the ability of five herbicides (Pendimethalin, Propizamide, Napropamide, Oxyflurofen and Simazine) in controlling weeds and their possible harmful effect on two Pinus species (Pinus halepensis, P. nigra ) and Quercus ilex in the nursery. Pendimethalin and Propizamide damaged seriously all tree species while Napropamide and Oxyflourfen did not produce any harmful effect and did not control effectively weeds. Simazine controlled weeds not affecting tree seedlings although it had to be applied periodically to mantain its effect on weeds.
Keywords: Herbicides; Nursery

ENSAYO DE TRATAMIENTOS HERBICIDAS EN CULTIVO DE TRES ESPECIES FORESTALES (P. halepensis, P. nigra y Q. ilex) EN VIVERO - CARRASCO MANZANO, I.; OCAÑA BUENO, L.; PEÑUELAS RUBIRA, J. L.; DOMINGUEZ LERENA, S. (II Congreso Forestal Español, 1997)
Weeds are one of the problems which more economic costs originates in forest nurseries due to their effect on crop growth. In spite of this, the effect of weeds on forest seedlings and their control in the nursery have not been much studied. In this study we have analysed the ability of five herbicides (Pendimethalin, Propizamide, Napropamide, Oxyflurofen and Simazine) in controlling weeds and their possible harmful effect on two Pinus species (Pinus halepensis, P. nigra ) and Quercus ilex in the nursery. Pendimethalin and Propizamide damaged seriously all tree species while Napropamide and Oxyflourfen did not produce any harmful effect and did not control effectively weeds. Simazine controlled weeds not affecting tree seedlings although it had to be applied periodically to mantain its effect on weeds.
The following values have no corresponding Zotero field: periodical: II Congreso Forestal Español pub-location: Pamplona
Keywords: Herbicides; Nursery

The implantation of cork oak (Quercus suber L) make use of herbicides: Preliminary results - Ortega, M; Villarroya, M; Montero, G; Chueca, M C; Garcia-Baudin, J M (CONGRESS 1997 - SOCIEDAD ESPANOLA DE MALHERBOLOGIA, PROCEEDINGS, 1997)
The response of cork oak (Quercus suber L.) to different rates of hexazinone, simazine and pendimetaline herbicides applied with a logaritmic sprayer, was studied. The effect on weeds of these herbicicles was also studied.
Keywords: Herbicides; Quercus suber L.

Selectivity and efficacy of some herbicides in forest plant nurseries. - Del Busto, A; Bimbo, B; Garcia-Espana, V; De Barreda, D G (CONGRESS 1997 - SOCIEDAD ESPANOLA DE MALHERBOLOGIA, PROCEEDINGS, 1997)
A experiment was conducted in a 4 especies of forest plants nurseries Quercus ilex L. Pinus halepensis Mill, Pinus pinea L. and Pistacia terebinthus L. with the following residual herbicides simazine, isoxaben, and thiazopyr. The treatment was done in preemergence of the weeds and the crops. Simazine, isoxaben and the mixture of both herbicides were selective in the four forest plants but thiazopir was phytotoxic.
Keywords: Herbicides; Pinus halepensis Mill; Pinus pinea L.; Pistacia terebinthus L.; plant nurseries; Quercus ilex L.; weeds control

Selectivity and efficacy of some herbicides in forest plant nurseries. - Del Busto, A.; Bimbo, B.; Garcia-Espana, V.; De Barreda, D. G. (CONGRESS 1997 - SOCIEDAD ESPANOLA DE MALHERBOLOGIA, PROCEEDINGS, 1997)
A experiment was conducted in a 4 especies of forest plants nurseries Quercus ilex L. Pinus halepensis Mill, Pinus pinea L. and Pistacia terebinthus L. with the following residual herbicides simazine, isoxaben, and thiazopyr. The treatment was done in preemergence of the weeds and the crops. Simazine, isoxaben and the mixture of both herbicides were selective in the four forest plants but thiazopir was phytotoxic.
The following values have no corresponding Zotero field: periodical: CONGRESS 1997 - SOCIEDAD ESPANOLA DE MALHERBOLOGIA, PROCEEDINGS pub-location: DEPARTAMENTO HORTOFRUTICULTURA , BOTANICA I JARDINERIA ETSEA, UNIVERSITAT LLEIDA, 25198 LLEIDA, SPAIN
Keywords: Herbicides; Pinus halepensis Mill; Pinus pinea L.; Pistacia terebinthus L.; plant nurseries; Quercus ilex L.; weeds control